State Agency Discretion and Entrepreneurship in Regulated Markets. (December 2020) - Grandy, Jake B.; Hiatt, Shon R.
Barriers to entry in regulated markets are frequently conceptualized as static features that must be removed or overcome if new entrants are to successfully enter a market. But government institutions regulating markets often comprise multiple levels that exist in tension with one another due to differing incentives and motivations. We argue that the principal–agent tension between elected officials and agency bureaucrats may render regulatory barriers to entry more malleable, even in the absence of formal policy changes. To test this proposition, we bring the administrative state center stage and examine how regulatory discretion—regulatory agencies' flexibility to interpret and implement public policies created by elected officials—can influence the market entry of new ventures. Using data on regulatory approval of hydroelectric facilities in the United States from 1978 to 2014, we find that increased state agency discretion improves outcomes for new ventures relative to incumbent firms by freeing regulatory agency officials to interpret and implement policies according to a professional motivation of public service and reducing incumbents' political influence.